Effects of Dietary Macronutrients on Plasma Lipid Levels and the Consequence for Cardiovascular Disease - Emilie Daoud; Celena Scheede-Bergdahl; Andreas Bergdahl (Journal of Cardiovascular Development and Disease, 2014)
Despite gaining focus, cardiovascular disease (CVD) remains the leading cause of death worldwide. Health promotion agencies have traditionally recommended diets that are low in fat in order to reduce CVD risk however, much debate remains about which dietary approaches are the most efficient for effective disease prevention. Common markers of CVD include elevated plasma triglycerides (TG) and low-density lipoprotein (LDL) cholesterol levels, as well as reduced high-density lipoprotein (HDL) cholesterol levels. While weight loss alone can significantly reduce markers of CVD, manipulating dietary macronutrient content contributes to the beneficial effects of weight loss and furthers the improvement of lipid profiles even without the alteration of total caloric intake. Considering the recent attention to diets that are low in carbohydrates rather than fat, it remains to be elucidated the beneficial effects of each diet type when establishing new recommendations for CVD prevention. This review aims to examine the effects of different macronutrient compositions on lipid markers, thus providing insight into the potential roles of various diet types in the targeted prevention against CVD.